2005
DOI: 10.1111/j.1365-2621.2005.tb09028.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-inflammatory Activities of Several Commonly Used Spices

Abstract: : Antioxidant and anti‐inflammatory activities are extensively used to screen chemo‐preventive foods. Five well‐known anticancer spices, ginger, red pepper, garlic, green onion, and leek, were selected and assessed in this study. Antioxidant function was evaluated based on the scavenging ability of the cation radical ABTS+. Moreover, anti‐inflammatory activity was determined based on the inhibitory effect of nitric oxide (NO) production by lipopolysaccharide (LPS)‐activated macrophages. The antioxidant activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 34 publications
5
52
0
4
Order By: Relevance
“…This could be very much contributed to antioxidant properties of the plant (Yin & Cheng 2003;Tsai et al 2005). These antioxidant effects are due to the activation and modification of several enzymes such as 3-hydroxy-3 methylglutaryl-CoA reductase, glutathione-s-transferase and catalase (Yin & Cheng 2003;Tsai et al 2005). Again, garlic inhibits Th1 and inflammatory cytokines while upregulating IL-10 production, thereby having anti-inflammatory, lymphoproliferative and immunomodulatory roles (Yin & Cheng 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be very much contributed to antioxidant properties of the plant (Yin & Cheng 2003;Tsai et al 2005). These antioxidant effects are due to the activation and modification of several enzymes such as 3-hydroxy-3 methylglutaryl-CoA reductase, glutathione-s-transferase and catalase (Yin & Cheng 2003;Tsai et al 2005). Again, garlic inhibits Th1 and inflammatory cytokines while upregulating IL-10 production, thereby having anti-inflammatory, lymphoproliferative and immunomodulatory roles (Yin & Cheng 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Again A. sativum caused marked decrease in the stress of animals due to parasitism as shown by FRAP values. This could be very much contributed to antioxidant properties of the plant (Yin & Cheng 2003;Tsai et al 2005). These antioxidant effects are due to the activation and modification of several enzymes such as 3-hydroxy-3 methylglutaryl-CoA reductase, glutathione-s-transferase and catalase (Yin & Cheng 2003;Tsai et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Murcia et al (2004) found that the aqueous extracts from nutmeg and ginger presented TEAC values higher than BHT. Tsai et al (2005) found that the ginger aqueous extract showed higher antioxidant activity than those from garlic and onion. On the other hand, garlic and onion methanolic extracts showed reasonable antioxidant capacity compared to other vegetables (Chun et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the results of the DPPH • scavenging were given in different unities, such as % activity (Cervato et al, 2000), % activity in relation to control (Capecka et al, 2005), % activity related to caffeic acid (Exarchou et al, 2002) or to pyrogallol (Nuutila et al, 2003), IC 50 or EC 50 Hinneburg et al, 2006;Kosar et al, 2005). Most of the results obtained with the ABTS radical has been reported as Trolox equivalent antioxidant capacity (TEAC) (Dorman et al, 2003;Murcia et al, 2004;Tsai et al, 2005), although ascorbic acid equivalent has also been used (Chun et al, 2005). Conflicting results regarding the free radical scavenging activity are also found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Sulphur and polyphenols present in garlic respond to the antibacterial, antifungal and antioxidant activity was carefully studied in a previous reports (Benkeblia, 2004(Benkeblia, , 2005Bozin, Mimica-Dukic, Samojlik, Goran, & Igic, 2008;Chung, 2006;Gorinstein, Leontowicz, Drzewiecki, et al, 2006a;Gorinstein, Leontowicz, Leontowicz, et al, 2006b;Nuutila, Puupponen-Pimia, Aarni, & Oksman-Caldentey, 2003;Pedraza-Chaverrí, Medina-Campos, & Segoviano-Murillo, 2007;Sener et al, 2005;Tsai, Tsai, & Ho, 2005). However, antioxidant activity of fruits and vegetables is affected by several factors as processing, the presence of additives, nutrients interactions, amongst others (Cardelle-Cobas, Moreno, Corzo, Olano, & Villamiel, 2005;Nicoli, Anese, & Parpinel, 1999;Pedraza-Chaverrí et al, 2007).…”
Section: Introductionmentioning
confidence: 99%